Tulungagung Batik Ethnoscience-Oriented E-Module Design On Chemical Bonding Materials - Anissa, Desi Dwi; Silfianah, Ifah (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
Tulungagung Batik Ethnoscience-Oriented E-Module Design On Chemical Bonding Materials. As time goes by, the field of education requires innovation in learning, especially in chemistry subjects, which does not diminish the culture inherent in Indonesia. Therefore, innovation is needed in the form of an ethnoscience-oriented e-module with the theme of Tulungagung batik culture on chemical bonding. The aim of this research is to create a product that adapts to the times but does not fade the culture, to find out the feasibility of this e-module product and to find out the level of student response to this e-module. This research uses the RnD (Research and Development) research method or research and development with a development model, namely 4D which was modified into 3D by Thiagarajan. The instrument used was a student response questionnaire. The results of this research on the feasibility aspect of the material got a percentage of 90% and on the aspect of media feasibility got a percentage of 94% with very feasible criteria, while the student responses showed a percentage of 86%. Therefore, this e-module product is very suitable for use. DOI: 10.23960/jppk.v12.i3.2023.08